The study of work-family enrichment and work-family conflict towards intrinsic career success among staff of education institute in Kuching Sarawak - Tay, Hui Ya (Universiti Malaysia Sarawak (UNIMAS), 2014)
The purpose of this study is to identify the influence of work family enrichment and work family conflict towards intrinsic career success among the staff in education institute at Kuching, Sarawak. 230 employees of the institute were participated in this study. Data were gathered through questionnaire analyzed by using Statistical Package for Social Science (SPSS) version 20. This study have two independent variables namely workfamily enrichment and work-family conflict and one dependant variables – intrinsic career success comprises the element of job satisfaction and career satisfaction. Throughout the statistical analysis – correlation analysis, it is found that there is a significant relationship between work-family enrichment and work-family conflict with job satisfaction. Based on these findings, recommendations and suggestions were made to the management.